THE INFLUENCE OF PANDEMICS AND POLITICAL UNCERTAINTY ON UTILITY VALUATION - Vučanović, Tijana (Ekonomija - teorija i praksa, 2022)
The Covid-19 virus and global political influences have changed consumer shopping priorities in line with reduced mobility, working from home and changed budget limits. Consumers directs their attention to products that they believe to provide greater usefulness (utility) in changed social circumstances. The purpose of this paper is to show the relationships between prices and budget limits for several observed products: butter and margarine (food products) and cough syrup and vitamin C (pharmaceutical products).